STRESS DISTRIBUTION IN UNBOUND AGGREGATE OF ROAD STRUCTURE: INFLUENCE OF SURFACE ROUGHNESS AND PARTICLE SHAPE - Hansson Ja.; Svensson P. (My University, 2001)
Aggregate used for road structures has to meet requirements regarding abrasion, strength and shape. These properties are largely influenced by the crushing operation. To improve these properties the aggregate can be cubicised in a vertical-shaft impact crusher. During this process, sharp edges will be rounded and the surface will be polished, which can have negative effects on road stability. This paper presents laboratory work on the load distribution by aggregate used in the unbound layers of the road structures. The aggregate used had different surface roughness and particle shape. The equipment used was a ring chamber consisting of 15 steel rings. The chamber's diameter was 320 mm and the height was 360 mm. Using this equipment, the stability of aggregates was studied with reference to particle shape and surface roughness for six types of aggregates by measuring the horizontal and the vertical stress that appear under a vertical loading. The grain size of the aggregates used was 8-11.2 mm. The aggregate was divided into three grades of surface roughness, depending on the level of cubicisation. Each level of surface roughness was divided into two groups, one flaky and one more cubic, in order to study the influence of aggregate shape. The laboratory tests showed that aggregate shape had an influence on the aggregate stability. Surface roughness also influenced the stability, but this was not as important as the aggregate shape.
Keywords: GRANULAR MATERIAL; AGGREGATE; STRESS DISTRIBUTION; AGGREGATE SHAPE; SURFACE ROUGHNESS